The future : six drivers of global change - Gore, Al, 1948- (New York : Random House, 2013)
"The consequential age we are living in will be remembered as one of the great turning points in civilization. Once we turn, though, where will we be? That is the compelling question Al Gore sets out to answer by examining the drivers of global change, connecting the dots among the social, economic, and political forces shaping our present and future. A rising global consciousness is forcing people around the world, but especially Americans, to rethink their basic assumptions about how the world works, and, even more fundamentally, how it should and can work. Borders matter less than ever. Technology is constantly reordering the way we live, think, work, learn, love, pray, and play"--
Includes bibliographical references (pages 379-387) and index.
Keywords: Globalization